How do you simplify #(x^-3)^-3x^3# and write it using only positive exponents?

1 Answer
Jul 19, 2017

Answer:

See a solution process below:

Explanation:

First, use this rule of exponents to simplify the expression on the left:

#(x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))#

#(x^color(red)(-3))^color(blue)(-3)x^3 => x^(color(red)(-3) xx color(blue)(-3))x^3 =x^9x^3#

Now, use this rule of exponents to complete the simplification:

#x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b))#

#x^color(red)(9)x^color(blue)(3) => x^(color(red)(9) + color(blue)(3)) = x^12#